Method for improving performance of micro-expansion mesocarbon microbeads in dual-ion battery
By using NADFOB additives in a dual -ion battery to decompose in advance on the surface of the micro -inflationary carbon micro -ball, a stable pre -CEI membrane layer is formed, which solves the problem of low efficiency of Kuron and graphite layer in the process of electrochemical activation. High Kuron efficiency and cycle stability.
Patent Information
- Application Number
- CN202411458735.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-18
AI Technical Summary
During the electrochemical activation process of micro-expanded mesophase carbon microspheres in the double-ion battery, the Coulomb efficiency is low and the graphite layer is severely peeled off, resulting in poor circulation stability.
Add 0.01-0.2 mol/L NaDFOB additive to the carbonate electrolyte to decompose in advance on the surface of micro-expanded mesophase carbon microspheres through an electrochemical activation process to form a stable pre-CEI film layer, blocking oxidative side decomposition reactions, and Optimize electrolyte composition to improve electrochemical performance.
By forming a stable pre -CEI membrane layer, the peeling of the graphite layer is suppressed, and the Kuron efficiency and cycle stability of the boltic battery are improved, and the battery's multiplier performance and long cycle stability significantly improve the battery.
Smart Images

Figure CN119340322A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dual-ion batteries, and in particular to a method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries. Background Art
[0002] At present, dual-ion batteries mainly use graphite as the cathode (positive electrode) material. In addition to the limited capacity, the interlayer spacing of graphite is small, which is not conducive to the deintercalation of larger anions during the charge and discharge process, and it is easy to cause the peeling of graphite sheets, resulting in a short cycle life. In addition, the working potential of graphite materials in dual-ion battery systems is greater than 5V. At this potential, common carbonate electrolytes will undergo severe oxidative side decomposition reactions, which directly affect the coulombic efficiency and cycle stability of dual-ion batteries.
[0003] The use of micro-expanded mesophase carbon microspheres as the cathode of the dual-ion battery has a larger graphite interlayer spacing due to the presence of multiple oxygen-containing functional groups between the layers of the material, which is more conducive to anion intercalation to provide higher capacity. After the electrochemical activation process at a high voltage of 5V, the maximum working cutoff potential of this material is only 4.5V, which can provide a capacity exceeding that of ordinary graphite positive electrode materials.
[0004] During the electrochemical activation of the micro-expanded mesophase carbon microspheres, the abundant oxygen-containing functional groups inside them undergo violent and complex oxidative side decomposition reactions with the carbonate electrolyte at a high voltage of 5V, resulting in extremely low coulombic efficiency and severe exfoliation of the graphite layer inside the carbon microspheres, which is not conducive to the normal operation of the subsequent dual-ion battery.
[0005] Therefore, it is urgent to develop a method to improve the cycling stability of micro-expanded mesophase carbon microspheres in dual-ion batteries. Summary of the invention
[0006] In order to solve the problems of the prior art, the present invention provides a method for improving the performance of micro-expanded mesophase carbon microspheres in a dual-ion battery.
[0007] In order to solve the above technical problems, the present invention is implemented by the following technical solutions: a method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries, the specific steps are as follows:
[0008] Step 1: Prepare positive and negative electrodes
[0009] Preparation of positive electrode sheet:
[0010] A carbonate electrolyte is selected, wherein the concentration of sodium salt contained in the carbonate electrolyte is in the range of 0.5-3 mol / L;
[0011] Under vacuum conditions, adding NaDFOB additive with a concentration of 0.01-0.2 mol / L to the carbonate electrolyte, mixing and stirring for a period of time to obtain a clear and transparent electrolyte;
[0012] The micro-expanded mesophase carbon microspheres are mixed with a conductive agent and a binder to form a slurry, which is coated on the surface of the aluminum foil current collector, and then dried and compacted to obtain a pole piece;
[0013] Under vacuum conditions, using the clear and transparent electrolyte obtained above, assembling the electrode obtained above with metal sodium and a glass fiber separator into a double-ion half-cell, and leaving it to stand for a period of time;
[0014] The dual-ion half-battery obtained above is subjected to an electrochemical activation process, and the dual-ion half-battery is charged at a constant current, the maximum cut-off voltage is set to 5V, the current density is 50-200mA / g, and the charge-discharge cycle is performed 1-6 times in a voltage window of 1.5-5V;
[0015] The electrochemically activated dual-ion half-cell is disassembled under vacuum conditions, the micro-expanded mesophase carbon microsphere electrode piece is taken out, and the micro-expanded mesophase carbon microsphere electrode piece is cleaned and dried with a corresponding organic solvent to obtain a micro-expanded mesophase carbon microsphere positive electrode piece having a thin, uniform and stable artificial solid electrolyte membrane layer CEI;
[0016] Preparation of negative electrode sheet:
[0017] The amorphous carbon material is mixed with a conductive agent and a binder to form a slurry, which is coated on the surface of a copper foil current collector, and dried and compacted to obtain a negative electrode sheet;
[0018] Step 2: assemble the positive electrode sheet and negative electrode sheet obtained in step 1, glass fiber separator, positive and negative electrode shells, spring sheet, gasket, and carbonate electrolyte in step 1 into a sodium ion-based dual-ion full battery, and let it stand for a period of time;
[0019] Step three: conducting an electrochemical performance test on the dual-ion full battery obtained in step two.
[0020] Preferably, in step 1, the sodium salt is any one of sodium hexafluorophosphate and sodium perchlorate, and the organic solvent in the carbonate electrolyte is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
[0021] Preferably, in step 1, a magnetic stirrer is used for mixing and stirring, and the stirring is performed for 18-32 hours.
[0022] Preferably, in step 1, the assembled dual-ion half-cell is left to stand for 18-32 hours.
[0023] Preferably, in step one, the amorphous carbon material includes hard carbon, soft carbon or a mixture of the two in any proportion; wherein the hard carbon-based material includes at least one of biomass-based hard carbon, phenolic resin-based hard carbon and asphalt-based hard carbon, and the soft carbon-based material includes at least one of petroleum coke, needle coke, carbon fiber, coke and carbon microspheres.
[0024] Preferably, in step 1, the conductive agent includes at least one of conductive carbon black, conductive graphite, and carbon nanotubes.
[0025] Preferably, in step 1, the binder includes at least one of polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), and polyvinylidene fluoride (PVDF).
[0026] Preferably, in step 2, the assembled sodium ion-based dual-ion full battery is left to stand for 18-32 hours.
[0027] Preferably, in step three, the electrochemical performance test includes rate performance, cycle performance and AC impedance.
[0028] The beneficial effects of the present invention are:
[0029] 1. The present invention utilizes an electrochemical activation process to add 0.01-0.2 mol / L of sodium difluorooxalatoborate (NaDFOB) to the electrolyte, so that it is decomposed in advance on the surface of the micro-expanded mesophase carbon microspheres to form a stable artificial solid electrolyte interface-pre-CEI film layer. The CEI film can play a barrier role and inhibit the serious oxidation side decomposition reaction between a large number of oxygen-containing functional groups in the graphite layer of the micro-expanded mesophase carbon microspheres and the electrolyte under high voltage; in addition, the electrode with the artificial CEI film layer after electrochemical activation can greatly weaken the anion solvation intercalation, improve the coulombic efficiency of the dual-ion battery, and at the same time make the battery have stable rate performance and cycle stability, further improving the electrochemical performance of the battery;
[0030] 2. The present invention optimizes the electrochemical activation process of the micro-expanded mesophase carbon microspheres by optimizing the electrolyte, thereby obtaining a dual-ion battery cathode material with a thin, uniform and stable artificial solid electrolyte membrane layer (CEI). After assembling the cathode with a hard carbon negative electrode, a sodium-based dual-ion full battery with excellent electrochemical performance can be obtained. Compared with the micro-expanded mesophase carbon microsphere cathode material whose electrochemical activation process is not optimized, it has more stable rate performance and long cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the relationship between time and voltage in the electrochemical activation process of various embodiments and comparative examples of the present invention;
[0032] Figure 2Schematic diagram of CV curves of the electrochemical activation process of various embodiments of the present invention and comparative examples;
[0033] Figure 3 is a schematic cross-sectional view of the electrode sheet after electrochemical activation under a microscope of Comparative Example 1 of the present invention;
[0034] Figure 4 is a schematic cross-sectional view of the electrode sheet after electrochemical activation under a microscope according to Example 1 of the present invention;
[0035] Figure 5 is a schematic diagram of the surface of the electrode sheet after electrochemical activation under a scanning electron microscope of Example 1 of the present invention;
[0036] Figure 6 is a schematic cross-sectional view of the electrode sheet after electrochemical activation under a scanning electron microscope according to Example 1 of the present invention;
[0037] Figure 7 is a schematic diagram of the pre-CEI film layer of Comparative Example 1 of the present invention under a transmission electron microscope;
[0038] Figure 8 is a schematic diagram of the pre-CEI film layer of Example 1 of the present invention under a transmission electron microscope;
[0039] Fig. 9 Schematic diagram of the rate and coulombic efficiency performance of the dual-ion half-cell of Example 1 of the present invention and Comparative Example 1;
[0040] Fig.10 Schematic diagram of voltage-specific capacity charge-discharge curves of dual-ion half-cells of Example 1 of the present invention and Comparative Example 1;
[0041] Fig.11 Schematic diagram of the long cycle performance of the dual ion half-cells of Example 1 of the present invention and Comparative Example 1 when the current density is 100 mA / g;
[0042] Fig.12 Schematic diagram of the long cycle performance of the dual ion half-cells of Example 1 of the present invention and Comparative Example 1 when the current density is 500 mA / g;
[0043] Fig.13 Schematic diagram of impedance of dual-ion half-cells of Example 1 of the present invention and Comparative Example 1;
[0044] Fig.14 Schematic diagram of the rate and coulombic efficiency performance of the dual-ion full battery of Example 1 of the present invention;
[0045] Fig.15 Schematic diagram of voltage-specific capacity charge-discharge curve of dual-ion full battery of Example 1 of the present invention;
[0046] Fig.16Schematic diagram of the long cycle performance of the dual-ion full battery of Example 1 of the present invention;
[0047] Fig.17 Schematic diagram of the electrochemical activation process of the dual-ion half-cell of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0049] Example 1
[0050] A method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries, the specific steps are as follows:
[0051] Step 1: Prepare positive and negative electrodes
[0052] Preparation of positive electrode sheet:
[0053] A carbonate electrolyte whose organic solvent is ethylene carbonate and ethyl methyl carbonate is selected, and 2 mol / L sodium hexafluorophosphate is selected as the sodium salt contained;
[0054] In a vacuum glove box, a NaDFOB additive with a concentration of 0.02 mol / L was added to the carbonate electrolyte, and mixed and stirred for 24 hours using a magnetic stirrer to obtain a clear and transparent electrolyte;
[0055] The micro-expanded mesophase carbon microspheres are mixed with a conductive agent and a binder to form a slurry, which is then coated on the surface of the aluminum foil current collector, and then dried and compacted and cut into pole pieces with a diameter of 13 mm.
[0056] In a vacuum glove box, using the clear and transparent electrolyte obtained above, the electrode obtained above, sodium metal, and a glass fiber separator are assembled into a double-ion half-cell and left to stand for 24 hours;
[0057] The dual-ion half-battery obtained above was subjected to an electrochemical activation process using an electrochemical instrument, and the dual-ion half-battery was charged at a constant current, with the maximum cut-off voltage set to 5V and the current density to 50mA / g, and the charge-discharge cycle was performed 6 times in a voltage window ranging from 1.5 to 5V;
[0058] The electrochemically activated dual-ion half-cell is disassembled in a vacuum glove box, the micro-expanded mesophase carbon microsphere electrode is taken out, and the micro-expanded mesophase carbon microsphere positive electrode with a thin, uniform and stable artificial solid electrolyte membrane (CEI) is obtained;
[0059] Preparation of negative electrode sheet:
[0060] The biomass-based hard carbon material is mixed with a conductive agent and a binder to form a slurry, which is then coated on the surface of the copper foil current collector, dried and compacted, and then cut into negative electrode sheets with a diameter of 13 mm;
[0061] Step 2: Use the positive electrode sheet and negative electrode sheet obtained in step 1, and assemble them with a glass fiber separator, a positive and negative electrode shell, a spring sheet, a gasket, and the carbonate electrolyte in step 1 into a sodium ion-based dual-ion full battery, and let it stand for 24 hours;
[0062] Step 3: Conduct an electrochemical performance test on the dual-ion full battery obtained in step 2. The electrochemical performance test includes rate performance, cycle performance and AC impedance.
[0063] Example 2
[0064] A method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries, the specific steps are as follows:
[0065] Step 1: Prepare positive and negative electrodes
[0066] Preparation of positive electrode sheet:
[0067] A carbonate electrolyte whose organic solvent is ethylene carbonate and ethyl methyl carbonate is selected, and 2 mol / L sodium hexafluorophosphate is selected as the sodium salt contained;
[0068] In a vacuum glove box, a NaDFOB additive with a concentration of 0.05 mol / L was added to the carbonate electrolyte, and mixed and stirred for 24 hours using a magnetic stirrer to obtain a clear and transparent electrolyte;
[0069] The micro-expanded mesophase carbon microspheres are mixed with a conductive agent and a binder to form a slurry, which is then coated on the surface of the aluminum foil current collector, and then dried and compacted and cut into pole pieces with a diameter of 13 mm.
[0070] In a vacuum glove box, using the clear and transparent electrolyte obtained above, the electrode obtained above, sodium metal, and a glass fiber separator are assembled into a double-ion half-cell and left to stand for 24 hours;
[0071] The dual-ion half-battery obtained above was subjected to an electrochemical activation process using an electrochemical instrument, and the dual-ion half-battery was charged at a constant current, with the maximum cut-off voltage set to 5V and the current density to 50mA / g, and the charge-discharge cycle was performed 6 times in a voltage window ranging from 1.5 to 5V;
[0072] The electrochemically activated dual-ion half-cell is disassembled in a vacuum glove box, the micro-expanded mesophase carbon microsphere electrode is taken out, and the micro-expanded mesophase carbon microsphere positive electrode with a thin, uniform and stable artificial solid electrolyte membrane (CEI) is obtained;
[0073] Preparation of negative electrode sheet:
[0074] The biomass-based hard carbon material is mixed with a conductive agent and a binder to form a slurry, which is then coated on the surface of the copper foil current collector, dried and compacted, and then cut into negative electrode sheets with a diameter of 13 mm;
[0075] Step 2: Use the positive electrode sheet and negative electrode sheet obtained in step 1, and assemble them with a glass fiber separator, a positive and negative electrode shell, a spring sheet, a gasket, and the carbonate electrolyte in step 1 into a sodium ion-based dual-ion full battery, and let it stand for 24 hours;
[0076] Step 3: Conduct an electrochemical performance test on the dual-ion full battery obtained in step 2. The electrochemical performance test includes rate performance, cycle performance and AC impedance.
[0077] Example 3
[0078] A method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries, the specific steps are as follows:
[0079] Step 1: Prepare positive and negative electrodes
[0080] Preparation of positive electrode sheet:
[0081] A carbonate electrolyte whose organic solvent is ethylene carbonate and ethyl methyl carbonate is selected, and 2 mol / L sodium hexafluorophosphate is selected as the sodium salt contained;
[0082] In a vacuum glove box, a NaDFOB additive with a concentration of 0.1 mol / L was added to the carbonate electrolyte, and mixed and stirred for 24 hours using a magnetic stirrer to obtain a clear and transparent electrolyte;
[0083] The micro-expanded mesophase carbon microspheres are mixed with a conductive agent and a binder to form a slurry, which is then coated on the surface of the aluminum foil current collector, and then dried and compacted and cut into pole pieces with a diameter of 13 mm.
[0084] In a vacuum glove box, using the clear and transparent electrolyte obtained above, the electrode obtained above, sodium metal, and a glass fiber separator are assembled into a double-ion half-cell and left to stand for 24 hours;
[0085] The dual-ion half-battery obtained above was subjected to an electrochemical activation process using an electrochemical instrument, and the dual-ion half-battery was charged at a constant current, with the maximum cut-off voltage set to 5V and the current density to 50mA / g, and the charge-discharge cycle was performed 6 times in a voltage window ranging from 1.5 to 5V;
[0086] The electrochemically activated dual-ion half-cell is disassembled in a vacuum glove box, the micro-expanded mesophase carbon microsphere electrode is taken out, and the micro-expanded mesophase carbon microsphere positive electrode with a thin, uniform and stable artificial solid electrolyte membrane (CEI) is obtained;
[0087] Preparation of negative electrode sheet:
[0088] The biomass-based hard carbon material is mixed with a conductive agent and a binder to form a slurry, which is then coated on the surface of the copper foil current collector, dried and compacted, and then cut into negative electrode sheets with a diameter of 13 mm;
[0089] Step 2: Use the positive electrode sheet and negative electrode sheet obtained in step 1, and assemble them with a glass fiber separator, a positive and negative electrode shell, a spring sheet, a gasket, and the carbonate electrolyte in step 1 into a sodium ion-based dual-ion full battery, and let it stand for 24 hours;
[0090] Step 3: Conduct an electrochemical performance test on the dual-ion full battery obtained in step 2. The electrochemical performance test includes rate performance, cycle performance and AC impedance.
[0091] Comparative Example 1
[0092] A method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries, the specific steps are as follows:
[0093] Step 1: Prepare positive and negative electrodes
[0094] Preparation of positive electrode sheet:
[0095] A carbonate electrolyte whose organic solvent is ethylene carbonate and ethyl methyl carbonate is selected, and 2 mol / L sodium hexafluorophosphate is selected as the sodium salt contained;
[0096] The micro-expanded mesophase carbon microspheres are mixed with a conductive agent and a binder to form a slurry, which is then coated on the surface of the aluminum foil current collector, and then dried and compacted and cut into pole pieces with a diameter of 13 mm.
[0097] In a vacuum glove box, the above-obtained electrode, sodium metal and glass fiber separator were assembled into a double-ion half-cell using the above-mentioned carbonate electrolyte and allowed to stand for 24 hours;
[0098] The dual-ion half-battery obtained above was subjected to an electrochemical activation process using an electrochemical instrument, and the dual-ion half-battery was charged at a constant current, with the maximum cut-off voltage set to 5V and the current density to 50mA / g, and the charge-discharge cycle was performed 6 times in a voltage window ranging from 1.5 to 5V;
[0099] The electrochemically activated dual-ion half-cell is disassembled in a vacuum glove box, the micro-expanded mesophase carbon microsphere electrode is taken out, and the micro-expanded mesophase carbon microsphere positive electrode with a thick, uneven and stable artificial solid electrolyte membrane (CEI) is obtained;
[0100] Preparation of negative electrode sheet:
[0101] The biomass-based hard carbon material is mixed with a conductive agent and a binder to form a slurry, which is then coated on the surface of the copper foil current collector, dried and compacted, and then cut into negative electrode sheets with a diameter of 13 mm;
[0102] Step 2: Use the positive electrode sheet and negative electrode sheet obtained in step 1, and assemble them with a glass fiber separator, a positive and negative electrode shell, a spring sheet, a gasket, and the carbonate electrolyte in step 1 into a sodium ion-based dual-ion full battery, and let it stand for 24 hours;
[0103] Step 3: Conduct an electrochemical performance test on the dual-ion full battery obtained in step 2. The electrochemical performance test includes rate performance, cycle performance and AC impedance.
[0104] The coulombic efficiency data of different numbers of electrochemical activation cycles of the above-mentioned embodiments and comparative examples are shown in Table 1 below:
[0105] Table 1 Comparison of coulombic efficiency of different cycles in electrochemical activation process
[0106]
[0107] It can be seen from Table 1 that, compared with Comparative Example 1, after adding the additive sodium difluorooxalatoborate (NaDFOB), the coulombic efficiency of each cycle of Examples 1 to 4 during the electrochemical activation process was greatly improved. Figure 2 Corresponding obvious changes can also be observed in the CV curves.
[0108] After electrochemical activation, the electrode interface was observed under a microscope, such as Figure 3 and Figure 4 It can be seen that Example 1 significantly inhibits the peeling of the graphite layer compared to Comparative Example 1. The electrode interface is observed using a scanning electron microscope. Figure 5 and Figure 6 It can be seen that the organic matter is uniformly attached to the surface of the micro-expanded mesophase carbon microspheres in the electrode of Example 1. The pre-CEI film layer is observed by transmission electron microscopy. Figure 7 and Figure 8 , it can be seen that the pre-CEI film layer of Example 1 is thin and uniform.
[0109] In terms of electrochemical performance, Example 1 has significantly improved rate and cycle performance compared to Comparative Example 1. Fig. 9 and Fig.10 It can be seen that at a current density of 2A / g, Example 1 can maintain a specific capacity of 94.5mAh / g, while Comparative Example 1 only has 52.2mAh / g, and the specific capacity of Example 1 is improved. Fig.11 At a low current density of 100 mA / g, Example 1 can cycle 1000 times and the capacity remains stable, while the battery capacity of the comparative example has seriously decayed after 650 cycles. Fig.12 At a high current density of 500 mA / g, the capacity of Example 1 was maintained at 70% after 2000 cycles, while that of Comparative Example 1 had decayed to 30% after 2000 cycles. Fig.13 , the impedance of Example 1 is also significantly reduced compared with Comparative Example 1.
[0110] After electrochemical activation, Example 1 of the present invention forms a stable artificial solid electrolyte interface membrane, which is matched with the biomass-based hard carbon material to form a sodium ion-based dual-ion full battery. Its rate performance, charge and discharge curve, and cycle performance are as follows: Fig.14 , Fig.15 , Fig.16 , Fig.14 It shows that its rate performance is excellent and it can still maintain a specific capacity of 60mAh / g at a current density of 20C. Fig.15 It shows that at a current density of 0.5C, the maximum specific capacity can reach 140.6mAh / g; Fig.16 It shows that after 300 cycles, the reversible specific capacity of 114.6 mAh / g can still be maintained.
[0111] The present invention utilizes an electrochemical activation process to add 0.01-0.2 mol / L of sodium difluorooxalatoborate (NaDFOB) into an electrolyte, so that it is decomposed in advance on the surface of micro-expanded mesophase carbon microspheres to form a stable artificial solid electrolyte interface film, namely a pre-CEI film layer; the CEI film layer can play a barrier role, inhibiting a large number of oxygen-containing functional groups in the graphite layer of the micro-expanded mesophase carbon microspheres from seriously oxidative side decomposition reactions with the electrolyte under high voltage; in addition, the electrode with the pre-CEI film layer after electrochemical activation can greatly weaken anion solvation intercalation, thereby improving the coulombic efficiency and cycle stability of the dual-ion battery.
[0112] The sodium ion-based dual-ion battery of the present invention uses a specific carbonate electrolyte and optimizes it, so that in the process of electrochemical activation, it has a thin and uniform and stable artificial solid electrolyte interface-a micro-expanded mesophase carbon microsphere positive electrode sheet of the pre-CEI film layer, and at the same time, by selecting hard carbon-based materials such as biomass-based hard carbon, phenolic resin-based hard carbon, and asphalt-based hard carbon as the negative electrode material, the rate performance, cycle stability and coulomb efficiency of the battery are effectively improved. Therefore, the sodium ion-based dual-ion battery of the present invention has the advantages of high specific energy and high stability, and provides new possibilities for the development of new energy storage technology.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents, and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries, characterized in that: The specific steps are as follows: Step 1: Prepare positive and negative electrodes Preparation of positive electrode sheet: A carbonate electrolyte is selected, wherein the concentration of sodium salt contained in the carbonate electrolyte is in the range of 0.5-3 mol / L; Under vacuum conditions, adding NaDFOB additive with a concentration of 0.01-0.2 mol / L to the carbonate electrolyte, mixing and stirring for a period of time to obtain a clear and transparent electrolyte; The micro-expanded mesophase carbon microspheres are mixed with a conductive agent and a binder to form a slurry, which is coated on the surface of the aluminum foil current collector, and then dried and compacted to obtain a pole piece; Under vacuum conditions, using the clear and transparent electrolyte obtained above, assembling the electrode obtained above with metal sodium and a glass fiber separator into a double ion half-cell, and leaving it to stand for a period of time; The dual-ion half-battery obtained above is subjected to an electrochemical activation process, and the dual-ion half-battery is charged at a constant current, the maximum cut-off voltage is set to 5V, the current density is 50-200mA / g, and the charge-discharge cycle is performed 1-6 times in a voltage window of 1.5-5V; The electrochemically activated dual-ion half-cell is disassembled under vacuum conditions, the micro-expanded mesophase carbon microsphere electrode piece is taken out, and the micro-expanded mesophase carbon microsphere electrode piece is cleaned and dried with a corresponding organic solvent to obtain a micro-expanded mesophase carbon microsphere positive electrode piece having a thin, uniform and stable artificial solid electrolyte membrane layer CEI; Preparation of negative electrode sheet: The amorphous carbon material is mixed with a conductive agent and a binder to form a slurry, which is coated on the surface of a copper foil current collector, and dried and compacted to obtain a negative electrode sheet; Step 2: assemble the positive electrode sheet and negative electrode sheet obtained in step 1, glass fiber separator, positive and negative electrode shells, spring sheet, gasket, and carbonate electrolyte in step 1 into a sodium ion-based dual-ion full battery, and let it stand for a period of time; Step three: conducting an electrochemical performance test on the dual-ion full battery obtained in step two.
2. The method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries according to claim 1, characterized in that: In the step 1, the sodium salt is selected from any one of sodium hexafluorophosphate and sodium perchlorate, and the organic solvent in the carbonate electrolyte is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
3. The method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries according to claim 1, characterized in that: In the step 1, a magnetic stirrer is used for mixing and stirring, and the stirring is performed for 18-32 hours.
4. The method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries according to claim 1, characterized in that: In the step 1, the assembled dual-ion half-cell is left to stand for 18-32 hours.
5. The method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries according to claim 1, characterized in that: In step one, the amorphous carbon material includes hard carbon, soft carbon or a mixture of the two in any proportion; wherein the hard carbon-based material includes at least one of biomass-based hard carbon, phenolic resin-based hard carbon and asphalt-based hard carbon, and the soft carbon-based material includes at least one of petroleum coke, needle coke, carbon fiber, coke and carbon microspheres.
6. The method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries according to claim 1, characterized in that: In the step 1, the conductive agent includes at least one of conductive carbon black, conductive graphite, and carbon nanotubes.
7. The method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries according to claim 1, characterized in that: In the step 1, the binder includes at least one of polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, and polyvinylidene fluoride.
8. The method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries according to claim 1, characterized in that: In the step 2, the assembled sodium ion-based dual-ion full battery is allowed to stand for 18-32 hours.
9. The method for improving the performance of micro-expanded mesophase carbon microspheres in dual-ion batteries according to claim 1, characterized in that: In the step three, the electrochemical performance test includes rate performance, cycle performance and AC impedance.
10. A sodium ion-based dual-ion full battery, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Activated mesocarbon microbeads, preparation method thereof and supercapacitor
CN104098078A
Preparation method of composite graphite, composite graphite and lithium ion battery
CN105098184A
Lithium battery cathode material, lithium battery cathode, preparation method of lithium battery cathode, and lithium battery
CN107742727A
Preparation method of modified mesocarbon microspheres as negative electrode material for sodium ion battery
CN108529585A
Active carbon and active carbon electrode for electric double layer capacitor, and electric double layer capacitor using the same
JP2004281555A